ANCAMAN PENYELUNDUPAN NARKOTIKA DI KAWASAN ASIA TENGGARA - Hardiansyah, Khelvin; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
One of the cross-border crimes is narcotics smuggling. This issue includes non-traditional security threats. This means that the problem is not only limited to one country but also transnational, or more broadly involving other countries. As is the case with drug trafficking, whose syndicates, networks and smuggling have now expanded. This study used qualitative research methods. The author uses document studies as a means of assisting researchers in collecting data or information by reading letters, announcements, meeting summaries, written statements on certain policies and other written materials to describe the threat of narcotics smuggling in the Southeast Asia region. The development of transnational crime as a result of globalization is also other factors related to the movement of people from one country to another or from one region to another. So, to overcome the spread of these crimes, legal instruments related to these types of crimes are needed, both national law and international law/international agreements and their protocols. Keywords: Threats, Transnational Crime, Narcotics Smuggling